AB0127 Anti-inflammatory and pro-apoptosis effects of 18beta-glycyrrhetinic acid in in vivo and in vitro models of rheumatoid arthritis. (12th June 2018) - Wang, M.; Huang, R.; ,
Abstract : Background: Rheumatoid arthritis (RA) is one of the most common autoimmune diseases and it affects 0.5%–2.0% of the human population worldwide. 1 Though disease modifying anti-rheumatic drugs (DMARDs) can improve the clinical condition of patients with RA, toxicities of these drugs will be accumulated with long-term use and the unwanted side effects still cannot be avoided. 18β-glycyrrhetinic acid (18β-GA), an active component of licorice, exhibits potential anti-cancer, anti-inflammatory, anti-allergic, and anti-microbial activities. 2 Moreover, 18β-GA has been elucidated to attenuate hepatotoxicity or nephrotoxicity caused by chemical drugs, included methotrexate(MTX)[. 2 These evidences suggested 18 β-GA may become a candidate for low toxicity RA therapy as the mechanism was revealed. Objectives: The aim of this study is to investigate the underline mechanism of 18β-GA on anti-inflammation and anti-proliferation in in vivo and in vitro models of RA. Methods: CIA rats were treated with 18β-GA, methotrexate, celecoxib and three combination therapies for 30 days. Paw swelling volume, thromboxane synthase (TxAS), proliferating cell nuclear antigenprotein (PCNA), interleukin (IL)−1β, IL-6, and thromboxane B2 (TxB2) were detected to assess the anti-inflammation and anti-proliferation effects of different treatments. To further study the potential mechanism, TNF-α-induced in vitro model was applied. With different treatments, cell proliferation was detected using MTS, meanwhile, cell cycle distribution and apoptosis were examined by flow cytometric analysis. Western blotting and real-time quantitative PCR were conducted to evaluate many moleculars that involved in interested pathways like COX-2/TxA2 pathway and AKT/FOXO3a pathway. Results: The paw swelling volume and histological data indicate that 18β-GA administration attenuates arthritis severity in rats with CIA. Lower level of IL-1β, IL-6, and TxB2 were observed in serum of 18β-GA group as compared with model group. In addition, synovial immunohistochemistry data shows that 18β-GA decreased about half of PCNA intensity induced by collagen. However, in vivo, all data exhibited no significant differences among groups with monotherapy and combination therapy. In vitro, 18β-GA inhibited the mRNA and protein levels of COX-2 and TxAS that induced by TNF-α in MH7A cell line. Both p-JNK and NF-κB1 (p50) were inhibited by 18β-GA as well as TxAS siRNA transfection. Moreover, 18β-GA inhibited MH7A proliferation in a time- and dose- dependent manner from MTS assay. Flow cytometric analysis revealed that 18β-GA induced cell apoptosis and caused G1-phase cell cycle arrest. Finally, AKT and FOXO3a were predominantly phosphorylated by TNF-α, whereas such effect was blocked by18β-GA treatment. Conclusions: This study has for the first time shown that 18β-GA has an inhibitory role in synovial cell inflammation and proliferation, which is, at least in part, dependent on the regulation of COX-2/TxA2pathway and AKT/FOXO3a pathway. Thus, 18β-GA should be regarded as a new potential drug candidate for RA therapy. References: [1] Korczowska I. Rheumatoid arthritis susceptibility genes: An overview. World J Orthop2014;5(4):544–9. [2] Mahmoud AM, et al. Methotrexate hepatotoxicity is associated with oxidative stress, and down-regulation of PPARgamma and Nrf2: Protective effect of 18beta-Glycyrrhetinic acid. Chem Biol Interact2017;270:59–72. Disclosure of Interest: None declared